Quantifying soil macrofauna in a Colombian watershed - Feijoo Martínez, Alexander; Knapp, E.B.; Lavelle, Patrick M.; Moreno, Alonso (International Center for Tropical Agriculture, 2001)
From April to September 1994, macrofauna density, total biomass, and species diversity of earthworms were measured across a range of land use types in the Cabuyal River watershed. The methodology recommended by the Tropical Soil Biology and Fertility (TSBF) Program was used. Macrofauna density, biomass, and diversity of earthworm species varied considerably across land use types, and depths. Initial factor analysis yielded three factors that accounted for 71.8% of the total variance in macrofauna density. High taxonomic unit (TU) values occur in the Andean forest (98 observed), decreasing dramatically in pastures (ranging from 28 to 13 TU) and farm lands (ranging from 31 to 18 TU).